DAMPAK PENGUNGKAPAN KINERJA SOSIAL (CSR) TERHADAP PROFITABILITAS PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI 2022-2024 - Amala Tussaleha; Tita Nawangsari , Ajeng (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study analyzes the impact of Corporate Social Responsibility (CSR) disclosure on the profitability of mining companies listed on the Indonesia Stock Exchange from 2022 to 2024. Given the sector's significant environmental footprint and rising stakeholder demands for sustainability, this research addresses the crucial link between CSR transparency and financial performance. Using a quantitative approach, linear regression was applied to data from 12 companies. CSR performance was measured against the Global Reporting Initiative (GRI) standards, and profitability was gauged by Return on Assets (ROA). The results show a strong positive relationship: a regression coefficient of 8.57 signifies that a one-point increase in the CSR disclosure score leads to an 8.57% increase in ROA. This finding supports legitimacy and stakeholder theories, confirming that transparent CSR reporting builds trust and enhances corporate reputation, which translates into better financial results. The study concludes that CSR disclosure is a strategic investment for sustainable value creation, not just a social duty. Consequently, management should integrate CSR into core business strategy, and investors should weigh these non-financial metrics in their decisions.